Transition from Hepatopulmonary Syndrome to Portopulmonary Hypertension: A Case Series of 3 Patients - Radhika Zopey; Irawan Susanto; Igor Barjaktarevic; Tisha Wang (Case Reports in Pulmonology)
Hepatopulmonary syndrome (HPS) and portopulmonary hypertension (PPHTN) are the two major pulmonary vascular complications of liver disease. While HPS is characterized by low pulmonary vascular resistance, PPHTN is defined by the presence of elevated pulmonary vascular resistance. Given these seemingly opposing pathophysiologic mechanisms, these conditions were traditionally felt to be mutually exclusive. In this series, we present three patients with severe hepatopulmonary syndrome who had spontaneous resolution of their HPS with the subsequent development of PPHTN. To our knowledge, this is the largest case series presented of this phenomenon in nontransplanted patients. One proposed mechanism for the occurrence of this phenomenon involves dysregulation of the same vascular signaling pathway, which may lead to both pulmonary vascular dilatations and pulmonary arterial remodeling in the same patient. Another theory involves the possible differential binding of endothelin-1, a vasoactive signaling peptide that induces vasoconstriction when bound to receptor A and vasodilation when bound to receptor B. Although the mechanisms for this phenomenon remain unclear, it is important to be vigilant of this phenomenon as it may change the patient's overall treatment plan, especially in regard to appropriateness and timing of liver transplant.